Pengaruh Media Pembelajaran Komik Digital Berbasis Cerita Fabel terhadap Keterampilan Bercerita pada Siswa Kelas V di Sekolah Dasar - Romadi, Syahlia Zahra; Dian Nuzulia Armariena; Marleni Marleni (FKIP, Universitas Palangka Raya, 2024)
This research was conducted with the aim of knowing the effect of fable-based digital comic learning media on storytelling skills in fifth grade students in elementary schools. The method used is the experimental method with the Posttest-Only Control Design, with data collection techniques through observation, documentation, testing, and recording. The validity of the research test used the expert judgment test on the storytelling skills instrument sheet. From the results of the validity, a test was carried out with 7 aspects of the assessment indicators of storytelling skills, which were then distributed to all samples of 50 students. Based on the results of the study, the average posttest result for students' storytelling skills in the experimental class was 72.31, while the average posttest result in the control class was 64.05. By testing the hypothesis of the posttest results of students in the experimental class and control class, t_count> t_(table) or 3.232> 1.677 is obtained. This means that H_O is rejected and H_a is accepted or the hypothesis which states that